Evaluating the impact of boxing on prefrontal cortex activation and cognitive performance: A pilot study using fNIRS technology and the Stroop test. - Muhammed Sıddık Çemç; Fatih Ağduman (PLoS ONE)
This research sets out to investigate the differences in hemoglobin concentration occurring in the prefrontal cortex (PFC) during the administration of the Stroop test in active amateur boxers and to compare the obtained data regarding chronic traumatic brain injury with those of healthy individuals. The research was conducted at the Atatürk University Neuropsychology Laboratory. Participants consisted of 6 male boxers, aged 19.66 ± 2.94 years, who had been actively boxing for 7.5 ± 3.8 years and had received at least high school level education, with right-hand dominance, and 8 healthy males, aged 19.62 ± 1.18 years, who had not engaged in any combat sports. fNIRS recordings were taken over the Prefrontal Cortex (PFC) while Stroop test stimuli were presented to the participants in a block design. The data were analyzed using the JASP program. Mann-Whitney U test was applied to evaluate the differences between groups in Stroop test data. The activation levels on the prefrontal cortex during the test were evaluated using the Repeated Measures ANOVA test. A significance level of p <0.05 was accepted for the analyses. In conclusion, compared to the control group, boxers demonstrated a significantly higher level of cerebral activation in the right dlPFC/vlPFC regions during the congruent task and in the right dmPFC as well as the left dmPFC/vmPFC/OFC regions during the incongruent task in the Stroop test. When the Stroop test results of the participants were evaluated between groups, it was found that although statistically insignificant compared to healthy subjects, boxers generally exhibited failure. In conclusion, it was found that boxers exhibit higher neural activation responses and lower cognitive performance during neurophysiological testing compared to healthy controls. These two conditions are thought to be interconnected and are considered to result from neural inefficiency.